Potent dengue virus neutralization by a therapeutic antibody with low monovalent affinity requires bivalent engagement. - Melissa A Edeling; S Kyle Austin; Bimmi Shrestha; Kimberly A Dowd; Swati Mukherjee; Christopher A Nelson; Syd Johnson; Manu N Mabila; Elizabeth A Christian; Joseph Rucker; Theodore C Pierson; Michael S Diamond; et al. (PLoS Pathogens, 2014)
We recently described our most potently neutralizing monoclonal antibody, E106, which protected against lethal Dengue virus type 1 (DENV-1) infection in mice. To further understand its functional properties, we determined the crystal structure of E106 Fab in complex with domain III (DIII) of DENV-1 envelope (E) protein to 2.45 Å resolution. Analysis of the complex revealed a small antibody-antigen interface with the epitope on DIII composed of nine residues along the lateral ridge and A-strand regions. Despite strong virus neutralizing activity of E106 IgG at picomolar concentrations, E106 Fab exhibited a ∼20,000-fold decrease in virus neutralization and bound isolated DIII, E, or viral particles with only a micromolar monovalent affinity. In comparison, E106 IgG bound DENV-1 virions with nanomolar avidity. The E106 epitope appears readily accessible on virions, as neutralization was largely temperature-independent. Collectively, our data suggest that E106 neutralizes DENV-1 infection through bivalent engagement of adjacent DIII subunits on a single virion. The isolation of anti-flavivirus antibodies that require bivalent binding to inhibit infection efficiently may be a rare event due to the unique icosahedral arrangement of envelope proteins on the virion surface.